Uji sitotoksisitas ekstrak etanol daun sirih cina (Peperomia pellucida [L.] Kunth) dengan metode brine Shrimp lethality test - Fadhlah Al-Uyun Nasution; Ridwanto Ridwanto; Zulmai Rani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The degree of harm a drug inflicts on cells, for instance, cancer cells, is known as its cytotoxicity. Cytotoxic substances can stop cancer cell proliferation, making anticancer medications possible. Plant extracts or active chemicals derived from plants can be used as herbal plants' anticancer agents. Among these is Chinese betel, a plant with numerous health benefits despite being frequently regarded as a weed. This study looked at the LC50 value using the BSLT method to identify the type of secondary metabolite chemicals and the cytotoxicity of Chinese betel leaf ethanol extract. This study looks at the number of Artemia salina deaths to characterise, screen for phytochemicals, and determine the cytotoxicity of Chinese betel leaves using the BSLT method- leaf larvae with LC50 values expressed. In the phytochemical screening test, Chinese betel leaves exhibited positive results for saponin, flavonoid, alkaloid, tannins, and steroids. The findings of the cytotoxicity test utilising probit analysis demonstrated that the ethanol extract of Chinese betel leaves is poisonous and may have anticancer properties, with an LC50 value of 335.7376 µg/mL.